Efektivitas Prinsip Redundansi dalam Presentasi Perkuliahan - Halim, Adriani; Yosanny, Agustinna; Soegandi, Andreas (Bina Nusantara University, 2012)
The purpose of this study is to study the application of redundancy principles by Richard Mayer on learning material used in class presentation. The principles are applied during the learning material development, using PowerPoint as the learning medium. The result of this study showes that the application of redundancy principle on learning material development provides positive result in helping students’understanding during teacher’s presentation.